Midwifery Care in Third Trimester Pregnant Women With Back Pain Discomfort in Clinics and Maternity Homes: Asuhan Kebidanan Pada Ibu Hamil Trimester III Dengan Ketidaknyamanan Nyeri Punggung di Klinik dan Rumah Bersalin - Sholikhah, Mariatus; Djauharoh, Djauharoh; Purwanti, Yanik (Universitas Muhammadiyah Sidoarjo, 2020)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are indicators to assess the degree of public health in a country. In Indonesia, MMR and IMR are still quite high, various efforts continue to be made to reduce this incidence, one of which is by implementing continuous midwifery care. During pregnancy, women will experience anatomical, physiological, and psychological changes that can cause discomfort, one of which is pain. back. This research method uses a descriptive method, the results of the study of back pain discomfort in third trimester pregnant women are physiological complaints and often occur in pregnant women. Efforts for pregnant women who experience back pain are asking for help from their families and health workers.